Organ‐Restricted Vascular Delivery of Nanoparticles for Lung Cancer Therapy. Issue 7 (13th May 2020) - Bölükbas, Deniz A.; Datz, Stefan; Meyer‐Schwickerath, Charlotte; Morrone, Carmela; Doryab, Ali; Gößl, Dorothee; Vreka, Malamati; Yang, Lin; Argyo, Christian; van Rijt, Sabine H.; Lindner, Michael; Eickelberg, Oliver; et al.
Abstract: Nanoparticle‐based targeted drug delivery holds promise for treatment of cancers. However, most approaches fail to be translated into clinical success due to ineffective tumor targeting in vivo. Here, the delivery potential of mesoporous silica nanoparticles (MSN) functionalized with targeting ligands for epidermal growth factor receptor and C─C chemokine receptor type 2 is explored in lung tumors. The addition of active targeting ligands on MSNs enhances their uptake in vitro but fails to promote specific delivery to tumors in vivo, when administered systemically via the blood or locally to the lung into immunocompetent murine lung cancer models. Ineffective tumor targeting is due to efficient clearance of the MSNs by the phagocytic cells of the liver, spleen, and lung. These limitations, however, are successfully overcome using a novel organ‐restricted vascular delivery (ORVD) approach. ORVD in isolated and perfused mouse lungs of Kras ‐mutant mice enables effective nanoparticle extravasation from the tumor vasculature into the core of solid lung tumors. In this study, ORVD promotes tumor cell‐specific uptake of nanoparticles at cellular resolution independent of their functionalization with targeting ligands. Organ‐restricted vascular delivery thus opens new avenues for optimized nanoparticles for lung cancer therapy and may have broad applications for other vascularized tumor types. Abstract : Despite their immense potential, clinical translation of nanomedicines is hampered by physicochemical and biological barriers impairing cell‐specific targeting especially in solid tumors. This study reports a novel approach using organ‐restricted vascular delivery (ORVD) with direct administration and recirculation of nanoparticles to enhance nanoparticle uptake in lung tumors. ORVD opens up new avenues for optimized nanotherapies.